Pengaruh Etos Kerja, Disiplin Kerja dan Budaya Organisasi terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Moderasi : Studi Kasus pada Diskuktrans ESDM, Karanganyar Jawa Tengah - Nathania Rara Agustia; Nur Achmad (MES Bogor, 2024)
Employee performance is one of the spearheads that an agency or organization needs to achieve its goals. It is necessary to know the factors that can help improve employee performance. This research aims to examine the role of organizational commitment in mediating the influence of work ethic, work discipline, organizational culture on employee performance. The research was carried out using a quantitative approach with a survey research type. Research data was collected using a questionnaire method. The population in this study were employees at the ESDM Diskuktrans, Karanganyar, Central Java using a total sampling technique. The data analysis technique uses SEM analysis using SmartPLS 4.0. The results of the research show that: Work ethic has a positive and significant effect on employee performance, Work discipline has no positive and significant effect on employee performance, Organizational culture has no positive and significant effect on employee performance expectations, Work ethic has a positive and significant effect on organizational commitment, Work discipline has an effect positive and significant on organizational commitment, and organizational culture has a positive and significant effect on organizational commitment. This research also shows that organizational commitment has no influence on the performance of employees of the ESDM Diskuktrans, Karanganyar, Central Java.